Preparation method of spherical lithium manganese iron phosphate positive electrode material with high compaction density
Through the steps of micro-nanoization, staging precipitation, granulation and high-temperature sintering, spherical lithium manganese phosphate positive electrode material with high compaction density is prepared, which solves the problem of insufficient compaction density of materials in the prior art and achieves high efficiency and low efficiency The production effect of cost.
Patent Information
- Application Number
- CN202411648253.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively improve the compaction density of lithium manganese iron phosphate positive electrode material, resulting in limited application in electric vehicles and energy storage systems.
Through the steps of raw material micro-nanoization, precursor graded precipitation, secondary spherical granulation and high-temperature sintering, a spherical lithium manganese phosphate positive electrode material with high compaction density was prepared. This method achieves graded precipitation by centrifugation at different rotation speeds, combining secondary granulation and high-temperature sintering to ensure high solids content and spherical shape of the material.
The high compaction density of lithium manganese iron phosphate cathode material has been achieved, reaching 2.68g/cm3, which improves the hardness and mechanical strength of the material, and reduces production costs and process complexity.
Smart Images

Figure CN119461300A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery positive electrode material preparation, in particular to a method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density. Background Art
[0002] Lithium iron manganese phosphate is a new type of positive electrode material for lithium-ion batteries. It is obtained by doping lithium iron phosphate with manganese elements. It inherits the advantages of lithium iron phosphate such as high safety, long cycle life and environmental friendliness. At the same time, due to the doping of manganese elements, the voltage platform of lithium iron manganese phosphate is improved, thereby improving the energy density of the battery. This feature makes lithium iron manganese phosphate have broad application prospects in fields such as electric vehicles and energy storage systems.
[0003] Lithium iron manganese phosphate cathode material has become a research hotspot in the field of lithium-ion batteries due to its excellent comprehensive performance. At present, the research on lithium iron manganese phosphate is mainly focused on improving its conductivity, compaction density and cycle stability, so as to achieve its wide application in electric vehicles and energy storage systems.
[0004] like Figure 1 As shown in the figure, the thermogravimetric curve of the high-temperature sintering process for preparing lithium iron manganese phosphate shows that in the range of 150-400°C, the sample has a large mass loss. Since the raw materials selected in the preparation process include carbonates, oxalates, ammonium salts, sulfates, carbon sources, etc., gas will inevitably be generated as the temperature rises; the large amount of gas generated in this process will cause structural collapse and the generation of internal pores inside the sample, thereby affecting the compaction density of the material. In this regard, researchers have made various attempts to improve its compaction density: for example, the invention patent application with the publication number CN115924874A, entitled A method for preparing a solid-phase high-pressure compacted lithium iron manganese phosphate positive electrode material and its product, discloses a scheme of nano-sized initial raw materials, mixing different nano-scale precursors at low temperature and then pressing them into embryos, and then sintering them at high temperature to obtain a lithium iron manganese phosphate positive electrode material with a high compaction density; however, the size and morphology of the lithium iron manganese phosphate particles prepared by this process cannot be controlled, and the experimental repeatability is poor. For example, in the invention patent application with publication number CN116986574A, entitled "A method for preparing high compacted density lithium manganese iron phosphate", it is disclosed that three lithium manganese iron phosphate materials with different particle sizes are mixed to prepare high compacted density lithium manganese iron phosphate, and its compacted density can reach 2.8g / cm 3 As above, the endurance of lithium manganese iron phosphate is improved, which is convenient for the promotion and application of lithium manganese iron phosphate batteries; however, the preparation process of this method is cumbersome, the process is complex, and the cost is high.
[0005] In summary, a method for preparing a spherical lithium manganese iron phosphate positive electrode material with high compaction density is urgently needed to solve this problem. Summary of the invention
[0006] The object of the present invention is to provide a method for preparing a spherical lithium iron manganese phosphate positive electrode material with a high compaction density, and to improve the compaction density of the lithium iron manganese phosphate positive electrode material through low-cost and simple and controllable steps.
[0007] To achieve the above object, the present invention provides the following technical solution: a method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density, comprising the following specific steps:
[0008] S1 Micro-nano raw material: raw materials including lithium source, phosphorus source, iron source and manganese source are mixed according to the process design ratio, and then the carbon source is added and ground to obtain a micro-nano sized primary precursor;
[0009] S2 Precursor graded precipitation: After slowly adding flocculant to a precursor slurry, the slurry is divided into at least two parts, centrifuged at different speeds, and the centrifuged slurries are mixed to obtain high solid content precursor aqueous slurries with different particle size distributions;
[0010] S3, secondary spherical granulation: after adjusting the viscosity of the precursor aqueous slurry to meet the granulation requirements using a thickener, a secondary granulation treatment is performed to obtain a spherical precursor powder;
[0011] S4. High temperature sintering: In a protective gas atmosphere, the powder is calcined and then cooled to obtain a high compaction density lithium manganese iron phosphate material.
[0012] Preferably, in the above step S1, the grinding and refining method is ball milling and / or sand milling, and the size range of the primary precursor particles after refining is 50 nm to 10 μm.
[0013] Preferably, in the above step S1, the lithium source is one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; the iron source is any one of ferrous sulfate, ferrous acetate, ferrous phosphate, ferric nitrate, ferrous oxalate, and ferric phosphate; the manganese source is any one of manganese sulfate, manganese acetate, manganese phosphate, manganese oxalate, manganese acetate, manganese trioxide, manganese dioxide, and manganese tetraoxide; the phosphorus source is any one of phosphoric acid, ammonium monohydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the carbon source is selected from one or more of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl alcohol, polyacrylonitrile, starch, cellulose, graphene, and carbon nanotubes; and the amount of carbon source added is 1 to 10 wt.% of the raw material.
[0014] Preferably, in the above step S2, the flocculant is one or more of polyferric sulfate, ferric sulfate, ferric chloride, polyphosphoferric chloride, and the amount of the flocculant added is 0.1 to 20 wt.% of the raw material.
[0015] Preferably, in the above step S2, the concentration of the prepared aqueous precursor slurry is 50-80 wt.%.
[0016] Preferably, in the above step S3, the thickener is selected from polyvinyl alcohol, sodium dodecylbenzene sulfonate, acrylic acid, polyvinyl pyrrolidone, sodium dodecyl sulfonate, polysulfonic acid, and the amount of the thickener added is 0.01 to 10 wt.% of the raw material.
[0017] Preferably, in the above step S3, the secondary granulation method is one or more of airflow impact method, spray drying, and vacuum spherical granulation.
[0018] Preferably, in the above step S4, the calcination temperature rising process includes: first placing the powder in a tubular furnace at 100-150°C for pre-sintering treatment under a protective gas atmosphere; then heating the powder in several sections at a temperature lower than the sintering temperature, controlling the heating rate of each section to not exceed 1°C / min, gradually increasing the insulation temperature of each section, and keeping each section for 30min-2h; finally, controlling the heating rate to not exceed 10°C / min, the sintering temperature to 650-800°C, and keeping the temperature for 8-12h.
[0019] Preferably, in the above step S4, before being divided into several stages, the protective gas atmosphere during pre-sintering is continued to be maintained, or the protective gas atmosphere is replaced with a mixed gas of reducing gas and argon, and the reducing gas is hydrogen, carbon monoxide or methane.
[0020] Preferably, in the above step S4, when the temperature is increased in several stages, the holding temperature is selected according to the inflection point of mass loss based on the thermogravimetric curve during the high-temperature sintering process to prepare lithium manganese iron phosphate.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The preparation method of the spherical lithium manganese iron phosphate positive electrode material with high compaction density has simple steps, low raw material cost and high production efficiency. The slurry with different particle size distributions is obtained only by centrifugation at different speeds. After mixing, the preparation of high solid content slurry is achieved. After the precursor aqueous slurry is granulated, the sphericity of the sample is guaranteed, and the hardness and mechanical strength of the powder are improved.
[0023] 2. The preparation method of the spherical lithium manganese iron phosphate positive electrode material with high compaction density is as follows: an iron-containing flocculant is added during the slurry graded precipitation process; in the subsequent high-temperature sintering process, pores are formed in the material due to the high-temperature generation of gas; the iron-containing flocculant can be used as a supplement of the iron element, and can further inhibit the generation of pores and volume expansion; the compaction density of the prepared spherical lithium manganese iron phosphate positive electrode material can reach 2.68g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is the thermogravimetric curve of the process of preparing lithium manganese iron phosphate by conventional high temperature sintering;
[0025] Figure 2 This is a SEM image of the product obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The preparation method of the spherical lithium manganese iron phosphate positive electrode material with high compaction density of the present invention is based on micro-nano particles, by adding additives to achieve the preparation of slurry with high solid content and different particle size distribution, and then performing secondary granulation to obtain a dense spherical precursor, and high-temperature sintering to obtain the product, which specifically includes:
[0027] S1. Micro-nano raw material: raw materials including lithium source, phosphorus source, iron source and manganese source are mixed according to the process design ratio, and then a carbon source is added and ground to obtain a micro-nano sized primary precursor, wherein the grinding and refining method can be ball milling and / or sand milling. Optionally, the particle size range of the refined primary precursor can be controlled to be 50nm to 10μm;
[0028] Usually, the lithium source in the above raw materials is one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; the iron source is any one of ferrous sulfate, ferric acetate, ferrous phosphate, ferric nitrate, ferrous oxalate, and ferric phosphate; the manganese source is any one of manganese sulfate, manganese acetate, manganese phosphate, manganese oxalate, manganese acetate, manganese trioxide, manganese dioxide, and manganese tetraoxide; the phosphorus source is any one of phosphoric acid, ammonium monohydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the carbon source is selected from one or more of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl alcohol, polyacrylonitrile, starch, cellulose, graphene, and carbon nanotubes; and the amount of carbon source added is generally 1 to 10 wt.% of the raw materials.
[0029] S2 Precursor graded precipitation: After slowly adding flocculant to a precursor slurry, the slurry is divided into at least two parts, centrifuged at different speeds, and the centrifuged slurries are mixed to obtain high solid content precursor aqueous slurries with different particle size distributions. For reference, the concentration can be 50-80wt.%, and if the water content is high, vacuum drying can be used to assist in reducing the water content;
[0030] It is worth noting that the centrifugation at different speeds in this step can obtain a particle size range at the corresponding speed, and this range is relatively controllable. The specific particle ratio required for the mixed slurry is not the research focus of the present invention. Therefore, the present invention only provides the idea of centrifugation at different speeds. The control of the speed can be achieved by a limited number of parameter adjustments under this idea. For reference here, the centrifugal speed difference between at least two portions can be greater than 300rpm to obtain a relatively different particle size. Its purpose has been disclosed in the prior art, which is to fill the gap between large-sized particles with small-sized particles. This is also one of the reasons for the high solid content. Therefore, the speed difference is only a reference, not a necessary limitation, and can be adjusted according to needs; accordingly, it can be divided into two or more portions according to a certain proportion, without equal proportion, and the mixing ratio can also be adjusted. Therefore, under the idea provided by the present invention, it is expected that the number, proportion and centrifugal speed of the precursor slurry can be adjusted.
[0031] In a preferred embodiment, the flocculant can be selected from one or more of polyferric sulfate, ferric sulfate, ferric chloride, polyphosphorus ferric chloride, and the amount of the flocculant added can be further selected to be 0.1 to 20 wt.% of the raw material.
[0032] S3, secondary spherical granulation: after adjusting the viscosity of the precursor aqueous slurry to meet the granulation requirements using a thickener, a secondary granulation treatment is performed. For reference, the secondary granulation method can be one or more of airflow impact method, spray drying, and vacuum spherical granulation. After the secondary granulation, a spherical precursor powder is obtained;
[0033] In a preferred embodiment, the above-mentioned thickener is selected from polyvinyl alcohol, sodium dodecylbenzene sulfonate, acrylic acid, polyvinyl pyrrolidone, sodium dodecyl sulfonate, and polysulfonic acid, and the addition amount of the thickener can be further selected to be 0.01 to 10 wt.% of the raw material.
[0034] S4, high temperature sintering: calcining the powder and then cooling it to obtain a high compaction density lithium manganese iron phosphate material;
[0035] The calcination temperature rise process may further include: first placing the powder in a tubular furnace at 100 to 150°C for pre-sintering in a protective gas atmosphere; then heating the powder in several sections at a temperature lower than the sintering temperature, controlling the heating rate of each section to not exceed 1°C / min, gradually increasing the insulation temperature of each section, and insulation of each section for 30min to 2h. For reference, the insulation temperature may be selected according to the thermogravimetric curve of the high-temperature sintering process for preparing lithium manganese iron phosphate, according to the mass loss inflection point, for example Figure 1 As shown in the figure, the temperature is around 257℃ and 380℃; finally, the heating rate is controlled not to exceed 10℃ / min, the sintering temperature is 650-800℃, and it is kept warm for 8-12h.
[0036] In addition, before being divided into several stages, the protective gas atmosphere during pre-sintering can be maintained, or the protective gas atmosphere can be replaced with a mixed gas of reducing gas and argon. The reducing gas is usually hydrogen, carbon monoxide or methane.
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] Example 1
[0039] S1: Micro-nano processing of raw materials: manganese oxalate, iron oxalate, lithium oxalate, and ammonium dihydrogen phosphate were added in a molar ratio of 0.6:0.3:1:1, and 2 wt.% graphene was added as a carbon source and sand-milled for 12 h to obtain a primary precursor with a D50 of 100 nm.
[0040] S2: Precursor graded precipitation treatment: Slowly drop 5 wt.% polyferric sulfate solution, divide it into two parts, and centrifuge at 300 rpm and 2000 rpm for 30 minutes respectively to obtain particles of different size distributions, and mix them to obtain a precursor aqueous slurry with a solid content of 60 wt.%.
[0041] S3: Secondary spherical granulation: Add 1wt.% polyvinyl alcohol dispersant, homogenize at 2000W power for 6h and 3000rpm to obtain a stable dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0042] S4: High temperature sintering: Place the powder in a tubular furnace for pre-sintering treatment under a nitrogen atmosphere, and heat it to 150°C at a rate of 2°C / min and keep it warm for 2 hours. Then, in a mixed atmosphere of hydrogen and argon, control the heating rate to 0.05°C / min, heat it to 257°C, and keep it warm for 1 hour. Continue to heat it to 400°C at a heating rate of 0.1°C / min, and keep it warm for 2 hours. Then, control the heating rate to 1°C / min, heat it to 700°C, and keep it warm for 10 hours; obtain carbon-coated lithium manganese iron phosphate material. After calcination, naturally cool it to obtain a high compaction density of 2.68g / cm 3 Lithium manganese iron phosphate material.
[0043] Comparative Example 1
[0044] S1: Micro-nano processing of raw materials: manganese oxalate, iron oxalate, lithium oxalate, and ammonium dihydrogen phosphate were added in a molar ratio of 0.6:0.4:1:1, and 2 wt.% graphene was added as a carbon source and sand-milled for 12 h to obtain a primary precursor with a D50 of 100 nm.
[0045] S2: Secondary spherical granulation: Add 1wt.% polyvinyl alcohol dispersant and directly prepare a precursor aqueous slurry with a solid content of 60wt.%. Homogenize at 2000W power ultrasound for 6h and 3000rpm to obtain a stably dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0046] S3: High temperature sintering: Place the powder in a tubular furnace for pre-sintering in a nitrogen atmosphere, and heat it to 150°C at a rate of 2°C / min and keep it warm for 2 hours. Then, continue to control the heating rate at 0.05°C / min in a nitrogen atmosphere, raise it to 257°C, and keep it warm for 1 hour. Continue to heat it to 400°C at a heating rate of 0.1°C / min, and keep it warm for 2 hours. Then, control the heating rate to 1°C / min, heat it to 700°C, and keep it warm for 10 hours; obtain carbon-coated lithium manganese iron phosphate material. After calcination, naturally cool it to obtain a compaction density of 1.8g / cm 3 Lithium manganese iron phosphate material.
[0047] The graded precipitation method of the present invention was not used in this comparative example, and the other steps were the same as those in Example 1. The compaction density of the obtained product was far lower than that in Example 1, which proved that the simple operation of centrifuging the slurry in batches at different speeds and then mixing them can greatly improve the product performance.
[0048] Example 2
[0049] S1: Micro-nano processing of raw materials: manganese acetate, ferrous acetate, lithium oxalate, and ammonium monohydrogen phosphate were added in a molar ratio of 0.6:0.4:1:1, and 8 wt.% glucose was added as a carbon source and ground in a ball mill for 10 h to obtain a primary precursor with a D50 of 200 nm.
[0050] S2: Precursor graded precipitation treatment: Slowly add 1wt.% ferric sulfate solution, divide it into two parts, and centrifuge at 100rpm and 500rpm for 30min respectively to obtain particles of different size distributions, and mix them to obtain an aqueous precursor slurry with a solid content of 70wt.%.
[0051] S3: Secondary spherical granulation: Add 5wt.% sodium dodecylbenzene sulfonate, homogenize at 1000W power for 6h and 2000rpm to obtain a stable dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0052] S4: High temperature sintering: Place the powder in a tubular furnace under a nitrogen atmosphere for pre-sintering treatment, and heat it to 150°C at a rate of 5°C / min and keep it warm for 2 hours. Then, in a mixed atmosphere of methane and argon, control the heating rate to 0.1°C / min, heat it to 260°C, and keep it warm for 2 hours. Continue to heat it to 380°C at a heating rate of 0.1°C / min, and keep it warm for 2 hours. Then, control the heating rate to 2°C / min, heat it to 450°C, and keep it warm for 30 minutes. Control the heating rate to 5°C / min, heat it to 700°C, and keep it warm for 10 hours; obtain carbon-coated lithium manganese iron phosphate material. After calcination, naturally cool it to obtain a high compaction density of 2.61g / cm 3 Lithium manganese iron phosphate material.
[0053] Example 3
[0054] S1: Micro-nano processing of raw materials: manganese sulfate, ferrous sulfate, lithium carbonate, and ammonium phosphate were added in a molar ratio of 0.6:0.28:1:1, and 5wt.% glucose and 3wt.% carbon nanotubes were added as carbon sources and sand-milled for 9h to obtain a primary precursor with a D50 of 300nm.
[0055] S2: Precursor graded precipitation treatment: Slowly add 8wt.% ferric chloride solution, divide it into two parts, and centrifuge at 200rpm and 800rpm for 30min respectively to obtain particles of different size distributions, and mix them to obtain an aqueous precursor slurry with a solid content of 80wt.%.
[0056] S3: Secondary spherical granulation: Add 0.01wt.% polyvinyl alcohol dispersant, homogenize at 2000W power for 6h and 3000rpm to obtain a stable dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0057] S4: High temperature sintering: Place the powder in a tubular furnace under a nitrogen atmosphere for pre-sintering treatment, and heat it to 150°C at 2°C / min and keep it warm for 2 hours. Then, control the heating rate to 0.05°C / min, heat it to 257°C, and keep it warm for 1 hour. Continue to heat it to 400°C at a heating rate of 0.1°C / min, and keep it warm for 2 hours. Then, control the heating rate to 1°C / min, heat it to 700°C, and keep it warm for 10 hours; obtain carbon-coated lithium manganese iron phosphate material. After calcination, cool it naturally to obtain a high compaction density of 2.56g / cm 3 Lithium manganese iron phosphate material.
[0058] Example 4
[0059] S1: Micro-nano processing of raw materials: manganese dioxide, iron oxide, lithium hydroxide, and diammonium hydrogen phosphate were added in a molar ratio of 0.6:0.37:1:1, and 8 wt.% polyacrylonitrile was added as a carbon source and ball-milled for 8 h to obtain a primary precursor with a D50 of 1 μm.
[0060] S2: Precursor graded precipitation treatment: 4 wt.% of polyferric phosphate chloride was added, divided into two parts, and centrifuged at 100 rpm and 900 rpm for 30 min respectively to obtain particles of different size distributions, and mixed to obtain an aqueous precursor slurry with a solid content of 65 wt.%.
[0061] S3: Secondary spherical granulation: 10 wt.% sodium dodecyl sulfate dispersant was added, and the precursor slurry was homogenized at 6000 W power for 3 h and 1000 rpm to obtain a stably dispersed precursor slurry. After the slurry was dispersed uniformly again, it was spray dried to obtain a secondary spherical precursor.
[0062] S4: High temperature sintering: The powder was placed in a tubular furnace for pre-sintering in an argon atmosphere, and the temperature was raised to 150°C at a rate of 5°C / min and kept at this temperature for 2 hours. Then, in a mixed atmosphere of carbon monoxide and argon, the heating rate was controlled to be 0.5°C / min, raised to 300°C, and kept at this temperature for 1 hour. The temperature was continued to be raised to 450°C at a rate of 1°C / min, and kept at this temperature for 2 hours. Next, the heating rate was controlled to be 5°C / min, raised to 650°C, and kept at this temperature for 10 hours; a carbon-coated lithium manganese iron phosphate material was obtained. After the calcination was completed, it was naturally cooled to obtain a compaction density of 2.51g / cm 3 Lithium manganese iron phosphate material.
[0063] Example 5
[0064] S1: Micro-nano processing of raw materials: manganese tetraoxide, iron phosphate, lithium carbonate and phosphoric acid were added in a molar ratio of 0.6:0.27:1:1, and 5 wt.% sucrose was added as a carbon source. The mixture was ground in a ball mill for 10 h to obtain a primary precursor with a D50 of 800 nm, which was then taken out and dried.
[0065] S2: Precursor graded precipitation treatment: Slowly add 10wt.% ferric sulfate solution, divide it into two parts, and centrifuge at 300rpm and 3000rpm for 30min respectively to obtain particles of different size distributions, and mix them to obtain a precursor aqueous slurry with a solid content of 50wt.%.
[0066] S3: Secondary spherical granulation: Add 3wt.% of acrylic acid dispersant, and homogenize at 1000W power for 3h and 1000rpm for 2h to obtain a stable dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0067] S4: High temperature sintering: Place the powder in a tubular furnace for pre-sintering treatment under an argon atmosphere, and heat it to 150°C at a rate of 5°C / min and keep it warm for 2 hours. Then, in a hydrogen and argon atmosphere, control the heating rate to be 1°C / min, heat it to 300°C, and keep it warm for 1 hour. Continue to heat it to 450°C at a heating rate of 0.5°C / min, and keep it warm for 2 hours. Then, control the heating rate to 2°C / min, heat it to 650°C, and keep it warm for 10 hours; obtain carbon-coated lithium manganese iron phosphate material. After calcination, cool it naturally to obtain a compaction density of 2.53g / cm 3 Lithium manganese iron phosphate material.
[0068] Example 6
[0069] S1: Micro-nano processing of raw materials: Manganese trioxide, ferrous phosphate, lithium acetate, and ammonium dihydrogen phosphate were added in a molar ratio of 0.6:0.4:1:1, and 2 wt.% citric acid and 5 wt.% polyvinyl alcohol were added as carbon sources and ground for 4 h under sand milling conditions to obtain a primary precursor with a D50 of 900 nm.
[0070] S2: Precursor graded precipitation treatment: Slowly add 8wt.% ferric chloride solution, divide it into two parts, and centrifuge at 500rpm and 3000rpm for 30min respectively to obtain particles of different size distributions, and mix them to obtain a precursor aqueous slurry with a solid content of 55wt.%.
[0071] S3: Secondary spherical granulation: Add 2wt.% of polysulfonic acid dispersant, and homogenize at 2000W power for 3h and 1800rpm for 2h to obtain a stable dispersed precursor slurry. After further uniform dispersion, spray drying is performed to obtain a secondary spherical precursor.
[0072] S4: High temperature sintering: The powder was placed in a tubular furnace for pre-sintering in an argon atmosphere, and the temperature was raised to 150°C at a rate of 5°C / min and kept at this temperature for 2 hours. Then, in a mixed atmosphere of methane and argon, the heating rate was controlled to be 0.2°C / min, the temperature was raised to 450°C, and the temperature was kept at this temperature for 2 hours. Next, the heating rate was controlled to be 2°C / min, the temperature was raised to 750°C, and the temperature was kept at this temperature for 6 hours to obtain a carbon-coated lithium manganese iron phosphate material. After the calcination was completed, it was naturally cooled, and the compaction density was obtained by a gas pulverizer with a density of 2.62g / cm 3 Lithium manganese iron phosphate material.
[0073] The above are only preferred embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope defined by the claims.
[0074] The matters not described in detail in the present invention are all known technologies to those skilled in the art.
Claims
1. A method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density, characterized in that: The specific steps include: S1 Micro-nano raw material: raw materials including lithium source, phosphorus source, iron source and manganese source are mixed according to the process design ratio, and then the carbon source is added and ground to obtain a micro-nano sized primary precursor; S2 Precursor graded precipitation: After slowly adding flocculant to a precursor slurry, the slurry is divided into at least two parts, centrifuged at different speeds, and the centrifuged slurries are mixed to obtain high solid content precursor aqueous slurries with different particle size distributions; S3, secondary spherical granulation: after adjusting the viscosity of the precursor aqueous slurry to meet the granulation requirements using a thickener, a secondary granulation treatment is performed to obtain a spherical precursor powder; S4. High temperature sintering: In a protective gas atmosphere, the powder is calcined and then cooled to obtain a high compaction density lithium manganese iron phosphate material.
2. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In the step S1, the grinding and refining method is ball milling and / or sand milling, and the size range of the primary precursor particles after refining is 50nm to 10μm.
3. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In the step S1, the lithium source is one of lithium carbonate, lithium hydroxide, lithium phosphate, and lithium dihydrogen phosphate; the iron source is any one of ferrous sulfate, ferrous acetate, ferrous phosphate, ferric nitrate, ferrous oxalate, and ferric phosphate; the manganese source is any one of manganese sulfate, manganese acetate, manganese phosphate, manganese oxalate, manganese acetate, manganese trioxide, manganese dioxide, and manganese tetraoxide; the phosphorus source is any one of phosphoric acid, ammonium monohydrogen phosphate, ammonium phosphate, ammonium dihydrogen phosphate, and diammonium hydrogen phosphate; the carbon source is selected from one or more of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl alcohol, polyacrylonitrile, starch, cellulose, graphene, and carbon nanotubes; and the amount of carbon source added is 1 to 10 wt.% of the raw material.
4. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S2, the flocculant is one or more of polyferric sulfate, ferric sulfate, ferric chloride, polyphosphorus ferric chloride, and the amount of the flocculant added is 0.1-20 wt.% of the raw material.
5. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In the step S2, the concentration of the prepared aqueous precursor slurry is 50-80 wt.%.
6. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In step S3, the thickener is selected from polyvinyl alcohol, sodium dodecylbenzene sulfonate, acrylic acid, polyvinyl pyrrolidone, sodium dodecyl sulfonate, and polysulfonic acid, and the amount of the thickener added is 0.01 to 10 wt.% of the raw material.
7. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In the step S3, the secondary granulation method is one or more of airflow impact method, spray drying, and vacuum spherical granulation.
8. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 1, characterized in that: In the step S4, the calcination temperature rising process includes: first placing the powder in a tubular furnace at 100-150°C for pre-sintering treatment under a protective gas atmosphere; then heating the powder in several sections at a temperature lower than the sintering temperature, controlling the heating rate of each section to not exceed 1°C / min, gradually increasing the insulation temperature of each section, and insulation of each section for 30min-2h; finally, controlling the heating rate to not exceed 10°C / min, the sintering temperature to 650-800°C, and insulation for 8-12h.
9. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 8, characterized in that: In the step S4, before being divided into several stages, the protective gas atmosphere during pre-sintering is continued to be maintained, or the protective gas atmosphere is replaced with a mixed gas of reducing gas and argon, and the reducing gas is hydrogen, carbon monoxide or methane.
10. The method for preparing a spherical lithium manganese iron phosphate positive electrode material with a high compaction density according to claim 8, characterized in that: In step S4, when the temperature is increased in several stages, the holding temperature is selected according to the mass loss inflection point based on the thermogravimetric curve during the high-temperature sintering process to prepare lithium manganese iron phosphate.
Citation Information
Patent Citations
Preparation method of solid-phase high-compaction lithium manganese iron phosphate positive electrode material and product thereof
CN115924874A
Preparation method of high-compaction-density lithium manganese iron phosphate
CN116986574A
Cited By
Preparation method of lithium ion battery manganese positive electrode material
CN121493917A